Queueing analysis of variable-bit-rate traffic over ATM switching - Bai, Lizhou (2010)
This thesis introduces a Variable-Bit-Rate (VBR) traffic model using a discrete-time 2 state Markov chain; or in other words a Markov Modulated Bernoulli Process (MMBP). The model we employed is not the simple ON/OFF model but a modified one, called High-Low (H/L) model. It has two non-zero-valued states corresponding to the relatively high-activity level and the low-activity level. The parameters of the model can readily be mapped to the key properties of the VBR traffic, such as the mean, the peak and the burstiness.